Governing policies and factors affecting the labor market integration of female accompanying spouses - Saurombe, Musawenkosi Donia; Zinatsa, Farirai (Frontiers in Sociology, 2023)
The main objective of this research was to determine the macro governing policies and factors that influence the integration of female accompanying spouses in the Free State, into the South African labor market. Utilizing a qualitative approach, thirteen one-on-one interviews, consisting of an initial purposive sample and a subsequent snowball sample, were conducted for data gathering. Thematic analysis was used to interpret the data. This study found that governing policies emerging from South Africa’s migration legislation, and factors such as spouse dependence, reinforcement of traditional gender roles, and restrictive employment legislation which forced deskilling of qualifications, mainly impacted the conduct of accompanying spouses concerning the labor market. This study contributes to the literature on labor market integration (LMI) from an understudied South-to-South perspective by exploring the experiences of skilled women migrants in the context of family migration. Further, it employs a neglected aspect of Michel Foucault’s theory of governmentality, to investigate the integration needs of accompanying spouses. The study’s qualitative approach renders the findings much less generalizable than a quantitative inquiry. Further, LMI research is highly context-specific, though some aspects of this research may apply to other contexts in the Global South. South Africa, which remains a key regional hub for migration in the Global South, has a complex migration governance framework that sets up a specific, while broadly exclusionary, macro context for accompanying spouses. This research can, to some extent, highlight issues that could inform policy.